Education and engagement : key elements to achieve and maintain a world free of chemical weapons - Suárez, Alejandra Graciela (2016)
Fil: Fil: Suárez, Alejandra Graciela. Universidad Nacional de Rosario. Facultad de Ciencias Bioquímicas y Farmacéuticas. Instituto de Química Rosario (IQUIR–CONICET); Argentina.